Glucose metabolism and its role in the maturation and migration of human CD1c+ dendritic cells following exposure to BCG - Triglia, Denise; Gogan, Karl M.; Keane, Joseph; O’Sullivan, Mary P. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Tuberculosis (TB) still kills over 1 million people annually. The only approved vaccine, BCG, prevents disseminated disease in children but shows low efficacy at preventing pulmonary TB. Myeloid dendritic cells (mDCs) are promising targets for vaccines and immunotherapies to combat infectious diseases due to their essential role in linking innate and adaptive immune responses. DCs undergo metabolic reprogramming following exposure to TLR agonists, which is thought to be a prerequisite for a successful host response to infection. We hypothesized that metabolic rewiring also plays a vital role in the maturation and migration of DCs stimulated with BCG. Consequently, we investigated the role of glycolysis in the activation of primary human myeloid CD1c+ DCs in response to BCG. Methods/results We show that CD1c+ mDC mature and acquire a more energetic phenotype upon challenge with BCG. Pharmacological inhibition of glycolysis with 2-deoxy-D-glucose (2-DG) decreased cytokine secretion and altered cell surface expression of both CD40 and CCR7 on BCG-challenged, compared to untreated, mDCs. Furthermore, inhibition of glycolysis had differential effects on infected and uninfected bystander mDCs in BCG-challenged cultures. For example, CCR7 expression was increased by 2-DG treatment following challenge with BCG and this increase in expression was seen only in BCG-infected mDCs. Moreover, although 2-DG treatment inhibited CCR7-mediated migration of bystander CD1C+ DCs in a transwell assay, migration of BCG-infected cells proceeded independently of glycolysis. Discussion Our results provide the first evidence that glycolysis plays divergent roles in the maturation and migration of human CD1c+ mDC exposed to BCG, segregating with infection status. Further investigation of cellular metabolism in DC subsets will be required to determine whether glycolysis can be targeted to elicit better protective immunity against Mtb.